Review article: the economic impact of the irritable bowel syndrome - Canavan, Caroline; West, Joe; Card, Timothy R. (Wiley, 2014)
Background: Irritable bowel syndrome (IBS) is a chronic functional disorder of the gastrointestinal system affecting a large number of people worldwide. Whilst it has no attributable mortality, it has substantial impact on patients' quality of life (QoL) and is associated with considerable healthcare resource use.